Development of Fuel Consumption Correction Factors for GTL Synthetic Diesel Fuel in Diesel Vehicles under Field Operating Conditions (Texas Journal of Engineering and Technology, 2026)
This paper proposes a compact operational method for adapting fuel-consumption norms when gas-to-liquid (GTL) synthetic diesel fuel is used in existing diesel vehicles. Field tests were conducted on an ISUZU NQR71PL vehicle operated on petroleum diesel and GTL fuel under comparable conditions. The test indicators included maximum speed, acceleration time to 60 km/h, and fuel consumption at 40-90 km/h. The maximum speed remained practically unchanged (104.17 and 105.50 km/h), while acceleration time increased from 15.91 to 16.86 s. GTL volumetric consumption exceeded diesel consumption by 4.56-6.10%, mainly because of the lower density and lower energy content per litre of GTL fuel. Speed-dependent correction factors of 1.046-1.061 were obtained, and an average value of 1.055 is recommended for preliminary fleet accounting. The results confirm that GTL fuel can be used without major vehicle modification, but separate consumption norms are required